Digital Wattpad Culture In Indonesia: Youth, Romance, And The Changing Practices Of Reading And Writing - Fiki Indah Yulianti (Politeknik Siber Cerdika Internasional, 2025)
This article explores digital Wattpad culture among Indonesian youth, focusing on how romance narratives shape changing practices of reading and writing. Using a qualitative descriptive design grounded in cultural and literacy studies, the research involves 15–24-year-old Wattpad users who actively read and/or write romance stories. Data were collected through online semi-structured interviews, digital ethnographic observation of Wattpad activities, and document analysis of selected romance texts. Thematic analysis reveals that Wattpad functions as an everyday literacy space where youth move from casual readers to more selective readers and, in many cases, to active writers. Romance emerges as the dominant genre, particularly subgenres such as school/campus romance, enemies-to-lovers, friends-to-lovers, and religious romance, which offer both familiarity and emotional intensity. Participants use Wattpad to explore identity, gender roles, love, and religiosity, while simultaneously negotiating global romance tropes with local Indonesian cultural norms. The findings also indicate perceived improvements in reading fluency, vocabulary, and narrative writing skills, alongside the development of audience awareness and critical judgment. However, the study also notes ambivalent effects, including the risk of unrealistic romantic expectations and normalization of problematic relationship models. The article argues that Wattpad should be recognized as part of Indonesia’s contemporary reading landscape and suggests that educators and policymakers can strategically leverage this platform to support youth literacy, provided that critical digital literacy is also fostered.